Eliciting the Functional Processes of Apologizing for Errors in Health Care - Marie M. Prothero; Janice M. Morse (Global Qualitative Nursing Research, 2017)
This article has been awarded GQNR’s Best Paper Award for the 2017 Volume The purpose of this article was to analyze the concept development of apology in the context of errors in health care, the administrative response, policy and format/process of the subsequent apology. Using pragmatic utility and a systematic review of the literature, 29 articles and one book provided attributes involved in apologizing. Analytic questions were developed to guide the data synthesis and types of apologies used in different circumstances identified. The antecedents of apologizing, and the attributes and outcomes were identified. A model was constructed illustrating the components of a complete apology, other types of apologies, and ramifications/outcomes of each. Clinical implications of developing formal policies for correcting medical errors through apologies are recommended. Defining the essential elements of apology is the first step in establishing a just culture in health care. Respect for patient-centered care reduces the retaliate consequences following an error, and may even restore the physician patient relationship.